The culture of science
1 online resource (xvi, 472 pages)
Keywords: "This book offers the first comparative account of the changes and stabilities of public perceptions of science within the US, France, China, Japan, and across Europe over the past few decades. The contributors address the influence of cultural factors; the question of science and religion and its influence on particular developments (e.g. stem cell research); and the demarcation of science from non-science as well as issues including the incommensurability versus cognitive polyphasia and the cognitive (in)tolerance of different systems of knowledge"--